2014
DOI: 10.3399/bjgp14x681853
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ attitudes on a healthy lifestyle: a survey of GPs in Flanders

Abstract: BackgroundPatients often consider health professionals to be role models for leading a healthy lifestyle but no data is available on tobacco, alcohol, or substance use among GPs in Flanders (northern Belgium).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…However, the study by Arvayeva et al assessing the prevalence of smoking among GPs in Ukraine shows a high percentage of smokers (57% among men and 15% among women) [42]. In contrast, a study of GPs in Flanders has shown that smoking is rare among doctors, as opposed to alcohol consumption [43]. Our study in the medical population showed the lower prevalence of smoking among primary care physicians compared to the general population [44].…”
Section: Discussionmentioning
confidence: 51%
“…However, the study by Arvayeva et al assessing the prevalence of smoking among GPs in Ukraine shows a high percentage of smokers (57% among men and 15% among women) [42]. In contrast, a study of GPs in Flanders has shown that smoking is rare among doctors, as opposed to alcohol consumption [43]. Our study in the medical population showed the lower prevalence of smoking among primary care physicians compared to the general population [44].…”
Section: Discussionmentioning
confidence: 51%
“…In addition, Galatea Foundation have conducted local studies towards PHC providers’ lifestyle habits, including alcohol consumption, and working conditions in Catalonia 17. In this regard, Saeys and Cammu24 suggested the behaviour of healthcare professionals demonstrated at work affected patient attitudes and their motivation towards making lifestyle changes, including the reduction or abstention from drug substances such as alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors usually lead the medical team, and as such, tend to see themselves as the ultimate in healthcare and would rather self-diagnose and treat as they deem fit than seek medical help from others. 26 Doctors had a better insight about health probably because they usually have higher level of training. Also, workers in clinical service areas were more likely than those in support services to have a right perception.…”
Section: Discussionmentioning
confidence: 99%